2002
DOI: 10.1002/1521-3757(20020703)114:13<2509::aid-ange2509>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A New Highly Efficient Ruthenium Metathesis Catalyst

Abstract: Catalytic olefin metathesis has recently become a powerful tool for carbon-carbon-bond formation in organic chemistry. [1] Over the last three years it has been demonstrated that ruthenium alkylidenes that bear N-heterocyclic carbene ligands, for example, 1 and similar analogues, exhibit extraordinary activity and stability. [2] Studies on the mechanism of olefin metathesis reactions have also been described. [2e,f] Phosphane-free catalyst 2 [3] has also recently been developed and studied. This catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 22 publications
0
49
0
1
Order By: Relevance
“…Grela and co-workers had previously shown that electron-donating methoxy groups on the aryl ring of the benzylidene ligand were very necessary to stabilize catalysts with methoxy-instead of propoxy-based alkoxy oxygens. [8][9][10] Therefore, Ru-based 'pseudo-halide' catalysts with CF 3 CO 2 -, CF 3 CF 2 CO 2 -, and CF 3 CF 2 CF 2 CO 2 -ligands were formulated from dichloride complexes with an a-asarone-derived ligand. 26 These three complexes possessed k p /k i values from 2 to 6 and facilitated living cyclopolymerizations of DEDPM which even rivaled the values obtained by Schrock catalysts; 26,86,87 however, in this series, the catalyst with the smallest fluorinated carboxylate (CF 3 CO 2 -) was the better initiator of the three examined.…”
Section: Diethyl Dipropargylmalonate (Dedpm)mentioning
confidence: 99%
“…Grela and co-workers had previously shown that electron-donating methoxy groups on the aryl ring of the benzylidene ligand were very necessary to stabilize catalysts with methoxy-instead of propoxy-based alkoxy oxygens. [8][9][10] Therefore, Ru-based 'pseudo-halide' catalysts with CF 3 CO 2 -, CF 3 CF 2 CO 2 -, and CF 3 CF 2 CF 2 CO 2 -ligands were formulated from dichloride complexes with an a-asarone-derived ligand. 26 These three complexes possessed k p /k i values from 2 to 6 and facilitated living cyclopolymerizations of DEDPM which even rivaled the values obtained by Schrock catalysts; 26,86,87 however, in this series, the catalyst with the smallest fluorinated carboxylate (CF 3 CO 2 -) was the better initiator of the three examined.…”
Section: Diethyl Dipropargylmalonate (Dedpm)mentioning
confidence: 99%
“…Catalysts 4 b [91] and 4 c, [92] which incorporate steric bulk ortho to the chelating isopropoxy moiety, are powerful metathesis initiators. We found that the use of only trace amounts of these precatalysts (only 0.005 mol % in the case of 4 c) effects ROM-CM reactions between a range of norbornenes or oxanorbornenes and allyltrimethylsilane in near quantitative yields.…”
Section: Ring-opening Cross-metathesismentioning
confidence: 99%
“…After 90 min at room temperature a conversion of 94% and after 120 min complete conversion was achieved (Table 1). However, catalyst 7 is even after activation with HCl less active then catalyst 4 which at a concentration of only 1 mol% is capable to convert 99% of 9 within 90 min into 10 (Table 1, entry 6) [15].…”
Section: Catalysis Experimentsmentioning
confidence: 99%
“…Selected bond lengths (Å ) and bond angles (°): Ru-O31 2.173(3), Ru-O41 2.062(3), Ru-N3 2.078(3), Ru-N4 2.107(3), Ru-C1 1.876(5), Ru-C8 2.088(4), N1-C8 1.353(5), N2-C8 1.348(5); O31-Ru-O41 84.55(12), O31-Ru-N3 77.69(12), O31-Ru-N4 82.49(12), O31-Ru-C1 170.43(15), O31-Ru-C8 96.94(14), O41-Ru-N3 160.57(12), O41-Ru-N4 78.73(12), O41-Ru-C1 102.0(2), O41-Ru-C8 93.41(13), N3-Ru-N4 91.10(13), N3-Ru-C1 94.8(2), N3-Ru-C8 96.45(14), N4-Ru-C1 91.8(2), N4-Ru-C8 172.14(14), C1-Ru-C8 89.7(2), N1-C8-N2 106.1(4).…”
unclassified